Genetic population structure of European anchovy in the Mediterranean Sea and the Northeast Atlantic Ocean using sequence analysis of the mitochondrial DNA control region - Viñas, Jordi; Sanz, Núria; Peñarrubia, Luis; Araguas, Rosa-Maria; García-Marín, José-Luis; Roldán, Maria-Inés; Pla, Carles (ICES journal of marine science, 2014)
Viñas, J., Sanz, N., Peñarrubia, L., Araguas, R-M., García-Marín, J-L., Roldán, M-I., and Pla, C. 2014. Genetic population structure of European anchovy in the Mediterranean Sea and the Northeast Atlantic Ocean using sequence analysis of the mitochondrial DNA control region. – ICES Journal of Marine Science, 71: 391–397. The European anchovy (Engraulis encrasicolus) exhibits a complex population structure in the Mediterranean Sea and Northeast Atlantic Ocean. To resolve the population genetic structure of this species, we surveyed sequence variability in the mitochondrial (mtDNA) control region in samples (n = 563) from 13 locations in the Northeast Atlantic, the Bay of Biscay, and the Mediterranean Sea. Based on pairwise ΦSTs, SAMOVA, and multidimensional scaling, a complicated population structure composed of multiple populations emerged. Combining these results with those from previous population studies based on mitochondrial and nuclear markers, we identified nine genetically differentiated European anchovy populations: (i) Canary Islands; (ii) Cádiz; (iii) Alborán Sea; (iv) Garona; (v) Arcachon and Donostia; (vi) a large population in the northwestern Mediterranean, including Cadaqués, Gulf of Lyon, Elba, and Sicily; (vii) southern Adriatic; (viii) northern Adriatic; and (ix) Aegean Sea. We suggest that independent management strategies should be implemented for each genetically differentiated population, and, in cases where several fisheries stocks are recognized within an area of genetic homogeneity, each stock should be managed separately.